Observer Design for a Core Circadian Rhythm Network. (8th July 2014) - Zhang, Yuhuan
Abstract : The paper investigates the observer design for a core circadian rhythm network in Drosophila and Neurospora . Based on the constructed highly nonlinear differential equation model and the recently proposed graphical approach, we design a rather simple observer for the circadian rhythm oscillator, which can well track the state of the original system for various input signals. Numerical simulations show the effectiveness of the designed observer. Potential applications of the related investigations include the real-world control and experimental design of the related biological networks.